2005
DOI: 10.1242/dev.02009
|View full text |Cite
|
Sign up to set email alerts
|

Specification and maintenance of the spinal cord stem zone

Abstract: Epiblast cells adjacent to the regressing primitive streak behave as a stem zone that progressively generates the entire spinal cord and also contributes to paraxial mesoderm. Despite this fundamental task, this cell population is poorly characterised, and the tissue interactions and signalling pathways that specify this unique region are unknown. Fibroblast growth factor (FGF) is implicated but it is unclear whether it is sufficient and/or directly required for stem zone specification. It is also not understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(115 citation statements)
references
References 78 publications
11
104
0
Order By: Relevance
“…FGF signaling is required for expression of the proneural gene Cash4 in the stem zone, which in turn induces the Notch ligand Delta1. 20,25 In addition, consistent with its proliferative activity, FGF signalling maintains Cyclin D2 expression in the caudal neural plate. 26 How FGF signaling inhibits the expression of genes involved in DV patterning of the neural tube is not clear.…”
Section: Fgf Signaling and The Establishment Of Spinal Cord Progenitorsmentioning
confidence: 84%
See 1 more Smart Citation
“…FGF signaling is required for expression of the proneural gene Cash4 in the stem zone, which in turn induces the Notch ligand Delta1. 20,25 In addition, consistent with its proliferative activity, FGF signalling maintains Cyclin D2 expression in the caudal neural plate. 26 How FGF signaling inhibits the expression of genes involved in DV patterning of the neural tube is not clear.…”
Section: Fgf Signaling and The Establishment Of Spinal Cord Progenitorsmentioning
confidence: 84%
“…In this region, known as the caudal stem cell zone, neural progenitors are maintained in a proliferative, undifferentiated state, by FGF signalling, mainly FGF8 ligand emanating from the surrounding presomitic mesoderm. [19][20][21] Moreover, within the caudal stem zone, FGF signalling appears to inhibit the expression of several factors that are later induced in neural progenitors. These include a number of the key DV patterning genes such as Pax6, Irx3 and Dbx1/2.…”
Section: Fgf Signaling and The Establishment Of Spinal Cord Progenitorsmentioning
confidence: 99%
“…Closer morphological inspection of the posterior tail bud identifies the dorsal epithelium of the neural tube (medullary cord), which runs further posteriorly than does the CNH in both mouse and chick, eventually becoming indistinct from the TBM. This region comprises the remnant of the stem zone, which contains neural progenitor cells for the spinal cord of the tail bud (Catala et al, 1995;Delfino-Machín et al, 2005;Diez del Coral et al, 2004). A striking difference between the chicken and the mouse is the lack of laminin staining of the posterior surface ectoderm of the chicken tail bud at these stages (arrowheads, Fig.…”
Section: Research Articlementioning
confidence: 99%
“…Previous studies have shown that the epiblast cells around the embryonic primitive streak have a dual fate, either penetrate beneath the CNP to create paraxial mesoderm (somite) forming ribs, vertebrae and muscle or reside in CNP to become neural precursor cell. It has been shown that FGF signaling has a major role in this decision and RA secreting from embryonic somite converts the neural precursor cells to the differentiated neurons through attenuating the FGF signaling [13][14][15] .…”
Section: Research Highlightmentioning
confidence: 99%